LEGAL INSTRUMENTS AND POLICIES FOR CONSUMER RIGHTS AND SAFETY IN ALBANIA: AN ANALYSIS - Manastirliu, Iris (International Journal of Legal and Social Order, 2025)
Consumer rights are a key element of public law, as they relate to the regulation of economic activities and the protection of individuals in their role as consumers within the market. This scientific paper presents an overview of how consumer rights are integrated and rooted in public law, which includes a regulatory role, state responsibility and preventive measures. Key elements include the right to information, security, choice, rectification and representation. Legal instruments include constitutional protection, legislation and regulatory agencies. Public policy implications include market regulation, public awareness campaigns and international cooperation. Administrative law regulates the relationship between individuals and public authorities, with agencies investigating and penalizing violations of consumer rights and administrative courts providing a platform to challenge regulatory decisions. Customer satisfaction is essential as it encourages repeat purchases, serves as a strong advertisement for the product and reflects the product's values ​​and beliefs.